Design selection of brake disc hybrid aluminium matrix composites reinforced with micro and nano particulates - Gan, Wei Kang (2016)
In the era of globalization, the use of automotive vehicles becoming more and more general. An brake disc play an important role in the vehicle and it is used to stop or decrease the velocity of the vehicle. The demand of metal matrix composites is greatly increased in fabricating the brake disc since it having a low density and high thermal conductivity. Over-heating will lead to the malfunction of the braking system and affect the safety of vehicle. Low weight of brake disc can decrease the use of fuel of the vehicle thus improve the fuel usage efficiency. This project will proposed suitable material and focus more on selecting best alternative designs for a brake disc. A suitable hybrid Al-MMCs material is identified from the research journal and compared with the conventional material, grey cast iron. Then, the most important parameters and specifications that affecting the design of brake disc are determined from QFD. From the outcomes of QFD, six alternatives design of brake disc are proposed and modeled into CATIA. The model of brake disc are then imported to ANSYS software for structural and thermal analysis. Finally, a decision making tool, AHP is used to chose the best design among the six alternatives design of brake disc.